Optimalisasi Limbah Kulit Kopi sebagai Pupuk Organik Cair untuk Pemberdayaan Masyarakat dalam Mendukung Pertanian Berkelanjutan di Desa Tamansari - Dlilah, Fa; Risma Herliana; Diva Nada Nabila; Ilham Fajar Nusantara; Pajar Arie Nugroho Madiono; Oktavia Citra Maharani; Rosita Setyaningrum; Firmansyah Aji Saputro; Kavin Bintang Alamsyah; Folista Affluent; Yuhana Erni Pertiwi; Dyah Purwita Wardani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Coffee plantations are one of Indonesia’s main commodities, producing up to 60% coffee husk waste from total production, most of which remains underutilized. This study aims to explore the potential use of coffee husk waste as raw material for liquid organic fertilizer (LOF) through fermentation. The method employed was anaerobic fermentation for seven days using EM4 bio-activator and molasses as an energy source for microorganisms. The results showed that the produced LOF contained essential macro-nutrients such as nitrogen, phosphorus, and potassium, as well as phytohormones including auxins and cytokinins that support plant growth. Application of coffee husk-based LOF positively affected robusta coffee seedling growth, indicating its potential as an eco-friendly fertilizer alternative while simultaneously reducing plantation waste pollution.